Layer-Structured Carbon Nanotube-Boron Nitride Nanotube Nanocomposites with Superior Multifunctional Shielding - Kim, Su-Yeon; Park, Sihun; Hong, Kyeongmin; Kim, Young-Kyeong; Choi, Yong-Seok; Jeong, Hyeondeok; Joo, Yongho; Jang, Se Gyu; Kim, Tae-Wook; Lee, Sang Seok (American Chemical Society, 2025)
As electronic systems increasingly operate in space environments, the demand for lightweight shielding materials capable of blocking electromagnetic interference, attenuating radiation, and managing heat continues to grow. However, conventional shielding materials either employ separate materials for each function or rely on simple mixing, leading to excessive weight gain, and particularly, random mixing of conductive and insulating components damages the inherent networks of each component, failing to exploit the synergistic effects of composites. This study presents a novel strategy to overcome these limitations by controlling nanofiller dimensionality and film stacking architecture in carbon nanotube (CNT) and boron nitride (BN) hybrid systems. Through comparative studies of two-dimensional hexagonal BN (hBN) and one-dimensional BN nanotubes (BNNT), we revealed that the one-dimensional morphology of BNNT maintains CNT percolation networks while forming effective interfacial interactions, whereas hBN sheets cause weak interfacial bonding. Based on this dimension-matched filler system, we designed a multilayer architecture with alternating conductive CNT and insulating BNNT layers, preserving the intrinsic properties of each layer while inducing synergistic effects. This CNT/BNNT multilayer structure demonstrated superior performance with enhanced mechanical strength, thermal conductivity, and particularly electromagnetic shielding effectiveness that exceeded uniformly mixed films by 11.7 dB in the X-band. Furthermore, the 10B isotope in BNNT layers can provide efficient neutron attenuation, enabling application as multifunctional materials for simultaneous electromagnetic and neutron shielding. By demonstrating the effects of nanofiller dimensionality and stacking architecture on composite performance enhancement, this work provides new directions for developing multifunctional shielding materials in aerospace applications.